2013
DOI: 10.1007/s10936-013-9248-4
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Learning in Individuals with Agrammatic Aphasia

Abstract: Implicit learning is a process of acquiring knowledge that occurs without conscious awareness of learning, whereas explicit learning involves the use of overt strategies. To date, research related to implicit learning following stroke has been largely restricted to the motor domain and has rarely addressed implications for language. The present study investigated implicit and explicit learning of an auditory word sequence in 10 individuals with stroke-induced agrammatic aphasia and 18 healthy age-matched parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 47 publications
(71 reference statements)
7
27
0
Order By: Relevance
“…The results conflict with the idea that agrammatic aphasia is associated with damage to domain-general mechanisms that subserve both sequence learning and syntactic processing (Christiansen et al, 2010). Although previous studies have shown impairments in implicit sequence learning co-occurring with syntactic impairments after brain injury (Christiansen et al, 2010; Zimmerer et al, 2014), the present results suggest otherwise and support previous studies showing implicit sequence learning ability in people with agrammatic aphasia (Goschke et al, 2001; Schuchard & Thompson, 2014; Schuchard & Thompson, in preparation). Future studies should be designed to examine factors such as lesion site that may contribute to the variability in implicit learning abilities in this population, which will further the understanding of the neural mechanisms underlying learning and language.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results conflict with the idea that agrammatic aphasia is associated with damage to domain-general mechanisms that subserve both sequence learning and syntactic processing (Christiansen et al, 2010). Although previous studies have shown impairments in implicit sequence learning co-occurring with syntactic impairments after brain injury (Christiansen et al, 2010; Zimmerer et al, 2014), the present results suggest otherwise and support previous studies showing implicit sequence learning ability in people with agrammatic aphasia (Goschke et al, 2001; Schuchard & Thompson, 2014; Schuchard & Thompson, in preparation). Future studies should be designed to examine factors such as lesion site that may contribute to the variability in implicit learning abilities in this population, which will further the understanding of the neural mechanisms underlying learning and language.…”
Section: Discussionsupporting
confidence: 84%
“…People with agrammatic aphasia have shown implicit learning of sequences in serial reaction time tasks (Goschke, Friederici, Kotz, & van Kampen, 2001; Schuchard & Thompson, 2014), but have also exhibited impairments in learning certain types of sequences (Goschke et al, 2001) and in learning the abstract underlying structures of sequences (Dominey, Hoen, Blanc, & Lelekov-Boissard, 2003). Additionally, a study that used a visual artificial grammar showed implicit learning deficits associated with agrammatic aphasia (Christiansen, Kelly, Shillcock, & Greenfield, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Goschke et al (2001) found sequential learning deficits specific to the linguistic domain (i.e. when learning phoneme sequences as opposed to visuomotor sequences), whereas Schuchard and Thompson (2014) found normal patterns of verbal sequence learning in people with agrammatic aphasia, possibly as a result of the larger sample size in the latter study.…”
Section: Introductionmentioning
confidence: 79%
“…However, studies examining sequential learning in people with agrammatic aphasia have shown mixed results. Several studies using serial reaction time (SRT) tasks, in which participants respond to a repeating sequence of stimuli, have shown evidence of sequential learning (Dominey et al, 2003; Goschke, Friederici, Kotz, & van Kampen, 2001; Schuchard, Nerantzini, & Thompson, 2017; Schuchard & Thompson, 2014). In contrast, artificial grammar learning studies, in which participants make judgments after exposure to multiple sequences of stimuli that follow an underlying rule structure, have shown abnormal learning ability in agrammatic aphasia (Christiansen et al, 2010; Zimmerer, Cowell, & Varley, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether this sort of adaptation occurs among aphasic participants, though some recent evidence consistent with preserved implicit learning in PWA would suggest that it might. Schuchard and Thompson (2014) show evidence of implicit learning in PWA on an artificial grammar learning task, and there is evidence that PWA may show surprisingly large structural priming effects, even for sentence types for which they show significant impairments (e.g., Hartsuiker & Kolk, 1998; Saffran & Martin, 1997). …”
mentioning
confidence: 95%